Dampak pelatihan literasi berbasis wacana dan praktik budaya lokal terhadap keterampilan membaca dan keterampilan hidup masyarakat - Indah Nurmahanani; Neneng Sriwulan; Hafiziani Eka Putri (Universitas Mulawarman, 2026)
The majority of people in remote areas have low literacy levels that hinder their employment, so literacy training for adults is needed. The purpose of this study was to investigate the impact of reading literacy training based on texts and local cultural practices on the community’s reading and life skills. A quasi-experimental method was used involving 225 people living in Wanayasa District, Ciawi Village, Purwakarta Regency, West Java Province. Data were collected through reading ability tests and interviews. Data analysis used descriptive analysis, paired t-tests, ANOVA, and effect sizes. The results of the study indicate that literacy training based on discourse and local cultural practices can improve the community’s reading and life skills. Improved reading competency includes increased reading comprehension, increased reading motivation, decreased reading anxiety, and decreased cognitive load. Furthermore, thematic analysis of interview results showed that literacy teaching interventions increased knowledge that supports employment, reading comprehension, and life skills. Therefore, literacy training based on discourse and local cultural practices can improve the community’s reading comprehension and life skills. This study implies that adult literacy training should be integrated with content needed to support life skills.